Ambassadors for Trinidad - Unknown (Sunday Guardian)
The Amral's Trinidad Cavaliers has made an unprecedented impact with their steelband music and the promotion of Trinidad and Tobago. References to newspaper headlines, international critics and testimonials from sponsors clearly verifies this. The tour proved to be one of the best promotional exercises ever.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Cultural diplomacy -- Trinidad and Tobago; Musicians -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago